A Patient-Centered Antipsychotic Medication Adherence Intervention: Results From a Randomized Controlled Trial. Issue 2 (February 2018) - Pyne, Jeffrey M.; Fischer, Ellen P.; Mittal, Dinesh; Owen, Richard
Abstract : Abstract: The purpose of this study was to develop and test a patient-centered and sustainable antipsychotic medication adherence intervention. The study design was a randomized controlled trial. Data from 61 patients diagnosed with schizophrenia or schizoaffective disorder were analyzed. The intervention included a checklist of barriers, facilitators, and motivators (BFM) for taking antipsychotic medications. The results of the checklist were summarized and a note was placed in the electronic medical record (EMR) and a hard copy was given to the patient. However, less than half of the BFM progress notes were placed in the EMR before the clinician visit as planned. The intervention significantly improved adherence at 6 months but not at 12 months and the intervention's effect on total Positive and Negative Syndrome Scale scores was not statistically significant. The BFM intervention is promising, but future studies are needed to improve the integration of the BFM intervention into typical clinic workflow.